Statistical modelling of rutting for low-volume roads in India - Chandrakasu Makendran (Građevinar)
This study considers a road rutting model better-suited for the flexible pavements in the low-volume roads of India. The rutting on a road directly affects various aspects such as the pavement performance, safety, driving comfort, and travel time. Accordingly, this study is conducted on 173 test sections of low-volume roads, and a mathematical rutting model is developed using a multiple regression analysis. In the model, the rutting is the response variable, whereas the commercial vehicles per day, rainfall, subgrade strength (as a modified structural number), and pavement age are the explanatory variables. The model is statistically validated and used to forecast road rutting and the effectiveness of the rutting prediction is confirmed. The error between the field data and estimated values is within 5 %.